If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9c + -4y = 0 Solving 9c + -4y = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '4y' to each side of the equation. 9c + -4y + 4y = 0 + 4y Combine like terms: -4y + 4y = 0 9c + 0 = 0 + 4y 9c = 0 + 4y Remove the zero: 9c = 4y Divide each side by '9'. c = 0.4444444444y Simplifying c = 0.4444444444y
| (5+2x)*4=5+8x | | 20/x=100 | | 6x=150 | | 7*8,333...-23=4*8,333...+2 | | 9x+4y+7z-5x+4z-5y= | | -5x-9=11-6x | | 35+x=27 | | 7x/4=14 | | 7x-23=4x+2 | | 7x-23=4x | | -6=9x+3 | | 1-5x+(2+x^2)x^2=0 | | x+4.7=63 | | 30=3x-3 | | 5x+5y=260 | | 1/2+4/5 | | x*5=300 | | 1/2+24/5 | | 3x+(4x+5)=180 | | x+2x+(7x+2)=22 | | 31/2+p=51/4 | | (X+3)(x+3)=100 | | 3u=42-4u | | 5(n-3)-3=12 | | 12-1*0+4/2 | | x-9/5+1/5=-x/15 | | x/6.5=4 | | 13+7m=97 | | c^2=-6-5c | | x-16=24 | | f/8+31=37 | | 2(2+1/3)=3/2n+1/2N-1/3 |